Groundwater Level Changes in Shallow Aquifer of Yogyakarta City, Indonesia: Distribution and Causes - Doni Prakasa Eka Putra; Rilo Restu Surya Atmaja; Liliane Manny (Geological Engineering Department Universitas Gadjah Mada, 2017)
The population in Yogyakarta City, Indonesia has increased since 1970, resulting in high groundwater utilization. This normally results in a decline of groundwater level in shallow aquifer beneath the city. However, expansion of the city and urbanization effects can also have the opposite effect and lead to a rise of groundwater levels due to urban recharge. This study investigates groundwater level changes in Yogyakarta City during a time period of 30 years between 1985 and 2015. Collected data in this research are groundwater level, rainfall, population density, sewer system, and land use. Overlaying various spatial information reveals a pattern of groundwater level rise in some areas of the city by 0–12 m, whilst in other areas a decline of 0–9 m is discovered. Rising groundwater levels are mainly found in areas moderate to high population density where sewer system networks have been installed. The rising of groundwater levels is this expected to be caused by urban recharge and sewers leakage.